Aspek Sosial Dalam Novel Orang-Orang Pulau Karya Giyan:Tinjauan Sosiologi Sastra Dan Relevansinya Dalam Pembelajaran Sastra Di Sekolah Menengah Atas - Setianingsih, Desi, Dr. Nafron Hasyim (2016)
The aims of this research are describing (1) the structural that builds novel Orang-orang Pulau by Giyan, (2) the social aspect within the novel, (3) the results relevance of this research concerning to implement it to the literary study in Senior High School (SMA). The method that uses in this research is belonging to descriptive qualitative method. The main object of this study is the social aspects. Where the data that required in this research are the paragraphs of Orang-orang Pulau. The primary data is gained from Orang-orang Pulau while the secondary data is gained from internet sources. Those articles are comments taken from the author‟s Facebook page. In this research‟s collecting data is settling in the way of scrutinizes and notes. As researcher depicts from other researches, this research will be validated the data in two methods, they are the triangulation theory and triangulation data. Following the technique of analyzing data is mapped out in dialectics method. Based on the analysis has been stretched off all around the writing, this research is gained three research results, those are (1) the structure that builds novel Orang-orang Pulau covering characters named Darso and Supini, the forward plotting story, setting of place settled in Kampung Katapang for 22 years and the idea including social inequality, (2) social aspect within the novel around poverties by the people of Kampung Katapang, as well as the social crimes such as the expulsion main character Darso from his home, disorganization family towards Nyai who leaved by Brodin and married with Napisa, people or society are always prioritized such matter aspect, the environments are limited by the higher and the lower, horrible educational system as well, and (3) the relevancy of this research is available on literary teaching of XI grade the first semester in accordance with the decree of SK 7 KD 7.2 for the KTSP and the XII grade 1 st semester relating to fiction stories to the Curriculum of 2013. Keywords: A Novel, the Social Aspect, Literary Sociology.